2022
DOI: 10.2174/1570159x19666210920091036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epigenetics in the Pathogenesis and Potential Treatment of Attention Deficit Hyperactivity Disorder

Abstract: : There is increasing evidence that dsyregulated epigenetic mechanisms of gene expression are involved in the pathogenesis of attention deficit hyperactivity disorder (ADHD). This review presents a comprehensive summary of the current state of research on the role of epigenetics in the pathogenesis of ADHD. The potential role of epigenetic drugs in the treatment of ADHD is also reviewed. Several studies suggest there are epigenetic abnormalities in preclinical models of ADHD and in ADHD patients. Regarding DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Moreover Luo et al [ 43 ] reported elevated H3 acetylation in hippocampal regions of offspring which is also involved in the pathophysiology of ADHD. [ 106 ] Similarly Scheider et al [ 41 ] had also reported that Pb exposure along with prenatal stress can result in PTHMs in hippocampal and frontal cortex region in a sex dependent manner. Extensive maternal exposure to Pb during postnatal and lactating periods can also alter the offspring's epigenome via transmission through lactating milk.…”
Section: Pthm a Potential Link Between Pb Exposure And Systemic Disea...mentioning
confidence: 99%
“…Moreover Luo et al [ 43 ] reported elevated H3 acetylation in hippocampal regions of offspring which is also involved in the pathophysiology of ADHD. [ 106 ] Similarly Scheider et al [ 41 ] had also reported that Pb exposure along with prenatal stress can result in PTHMs in hippocampal and frontal cortex region in a sex dependent manner. Extensive maternal exposure to Pb during postnatal and lactating periods can also alter the offspring's epigenome via transmission through lactating milk.…”
Section: Pthm a Potential Link Between Pb Exposure And Systemic Disea...mentioning
confidence: 99%
“…29 Moreover, great advances have been made in uncovering epigenetic mechanisms underlying ADHD development. 30,31 For instance, ADHD-PRS was also shown to be correlated with global and peripheral DNA methylation levels. [32][33][34] Despite such remarkable advances in both genetics and neuroimaging investigations of ADHD, the putative mechanisms by which polygenic architecture influences clinical features via functional neurodevelopment remain largely speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ADHD‐PRS is also associated not only with hyperactivity/impulsivity symptoms, but also with genetic vulnerability for a myriad of psychiatric symptoms and disorders in children and in the general population 29 . Moreover, great advances have been made in uncovering epigenetic mechanisms underlying ADHD development 30,31 . For instance, ADHD‐PRS was also shown to be correlated with global and peripheral DNA methylation levels 32–34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation